2014
DOI: 10.1038/ismej.2014.39
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial epibionts of Daphnia: a potential route for the transfer of dissolved organic carbon in freshwater food webs

Abstract: The identification of interacting species and elucidation of their mode of interaction may be crucial to understand ecosystem-level processes. We analysed the activity and identity of bacterial epibionts in cultures of Daphnia galeata and of natural daphnid populations. Epibiotic bacteria incorporated considerable amounts of dissolved organic carbon (DOC), as estimated via uptake of tritiated leucine: three times more tracer was consumed by microbes on a single Daphnia than in 1 ml of lake water. However, ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
53
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(62 citation statements)
references
References 78 publications
(77 reference statements)
6
53
0
Order By: Relevance
“…to be the dominant taxon, this is in accordance with earlier studies who also found this taxon to be a major constituent of the Daphnia microbiota (Freese & Schink, 2011;Eckert & Pernthaler, 2014;Gorokhova et al, 2015). However, by specifically characterizing the gut microbiota, we found that in our cultures Aeromonas sp.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…to be the dominant taxon, this is in accordance with earlier studies who also found this taxon to be a major constituent of the Daphnia microbiota (Freese & Schink, 2011;Eckert & Pernthaler, 2014;Gorokhova et al, 2015). However, by specifically characterizing the gut microbiota, we found that in our cultures Aeromonas sp.…”
Section: Discussionsupporting
confidence: 78%
“…Daphnia is known to harbor high numbers of bacteria on the surface of its body and in its gut (Grossart et al, 2010;Eckert & Pernthaler, 2014), and Qi et al (2009) showed that several bacterial taxa are consistently found in affiliation with Daphnia, even in geographically separated populations, indicating a highly specific association between Daphnia and its microbiota. Notably, the β-proteobacterial genus Limnohabitans (Comamonadaceae) seems to be a major constituent of the Daphnia microbiota (Freese & Schink, 2011;Eckert & Pernthaler, 2014;. Sison-Mangus et al (2014) showed, by comparing bacteria-free Daphnia with conventional ones, that the relationship between D. magna and its microbiota is mutualistic, as removing the microbiota results in decreased growth, survival and reproduction of the host.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This ‘hitch hiking’ provides bacteria with a means of increasing their dispersal (Grossart et al ., ), and, in turn, is also beneficial to their hosts (Sison‐Mangus et al ., ; Peerakietkhajorn et al ., ). Moreover, the consumption of zooplankton together with their attached microflora by fish may represent a shortcut within microbial food webs that increases DOC transfer efficiency by several orders of magnitude (Eckert and Pernthaler, ).…”
Section: Attached Bacteriamentioning
confidence: 99%
“…Limnohabitans bacteria from the R-BT cluster are omnipresent in a wide variety of pHneutral or alkaline freshwater habitats (16). However, they have been also found as microflora in the digestive tract of algivorous Daphnia magna (22) or as epibionts in filter combs of Daphia galeata (23). Thus, it seems that the main substrates supporting their rapid growth in situ are alga-derived substances (19,24,25).…”
mentioning
confidence: 99%